2014
DOI: 10.3233/bme-141028
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated GDNF protects bone marrow mesenchymal stem cells against apoptosis induced by hydrogen peroxide

Abstract: In this study, the effects of adenoviral-mediated glial cell line-derived neurotrophic factor (Ad-GDNF) on apoptosis of cultured bone marrow mesenchymal stem cells (BMSCs) induced by hydrogen peroxide (H 2 O 2 ) were investigated. After BMSCs infected with Ad-GDNF were treated with 500 μM H 2 O 2 at 37°C for 1 h, lactate dehydrogenase (LDH), MTT and TUNEL methods were used to detect cell viability and apoptosis. In addition, the levels of GDNF in the supernatants in BMSCs cultures were detected by ELISA, pro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…SSCs that are capable of repopulating spermatogenesis have ceased due to the side effect of chemotherapy to the SSC niche, including GDNF reduction, inflammation, and apoptosis ( Harman and Richburg, 2014 ; Morimoto et al., 2021 ; Qian et al., 2020 ; Zhang et al., 2013 ). Apart from the key regulator of SSC self-renewal, GDNF also involves anti-inflammation and anti-apoptosis, which made it essential for SSC propagation in vivo and in vitro ( Gao et al., 2014 ; Kanatsu-Shinohara et al., 2003 ; Kubota et al., 2004 ; Masaki et al., 2018 ; Meng et al., 2000 ; Sharma and Braun, 2018 ; Tadokoro et al., 2002 ; Tan et al., 2020 ; Wang et al., 2019 ). Therefore, we set up a drug screening system to identify potential candidates that promote mSSC self-renewal independent of GDNF, which may provide a hint for SSC recovery in defected testis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSCs that are capable of repopulating spermatogenesis have ceased due to the side effect of chemotherapy to the SSC niche, including GDNF reduction, inflammation, and apoptosis ( Harman and Richburg, 2014 ; Morimoto et al., 2021 ; Qian et al., 2020 ; Zhang et al., 2013 ). Apart from the key regulator of SSC self-renewal, GDNF also involves anti-inflammation and anti-apoptosis, which made it essential for SSC propagation in vivo and in vitro ( Gao et al., 2014 ; Kanatsu-Shinohara et al., 2003 ; Kubota et al., 2004 ; Masaki et al., 2018 ; Meng et al., 2000 ; Sharma and Braun, 2018 ; Tadokoro et al., 2002 ; Tan et al., 2020 ; Wang et al., 2019 ). Therefore, we set up a drug screening system to identify potential candidates that promote mSSC self-renewal independent of GDNF, which may provide a hint for SSC recovery in defected testis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mSSCs derived from the LOVA group were capable for spermatogenesis that generate fertile offspring after being transplanted into the testes of recipient mice, indicating that LOVA ensures normal mSSC functions while faithfully promoting mSSC self-renewal. Further mechanism analysis suggested effects of LOVA on SSCs through multiple layers, including promotion of self-renewal and cell cycle as well as inhibition of inflammation and apoptosis, which might partially substitute and fulfill the role of GDNF in mSSC proliferation ( Gao et al., 2014 ; Kubota et al., 2004 ; Masaki et al., 2018 ; Meng et al., 2000 ; Sharma and Braun, 2018 ; Tadokoro et al., 2002 ; Wang et al., 2019 ), as statins inhibit HMGCR, the rate-limiting enzyme of the L-mevalonate pathway, thereby preventing the formation of downstream metabolites ( Assmus et al., 2003 ; Zeiser, 2018 ; Zeiser et al., 2009 ). Hence, we tested and found that the addition of downstream metabolites such as GPP, FPP, and squalene were capable of abolishing LOVA-mediated apoptosis prevention to mSSCs, suggesting that inhibitory effects of LOVA are dependent on HMGCR.…”
Section: Discussionmentioning
confidence: 99%